RUMAH RESTORATIVE JUSTICE KOTA SAMARINDA SEBAGAI WADAH PEMBERIAN PERLINDUNGAN HUKUM DENGAN PRINSIP NILAI KEADILAN - Hendrik Kusnianto (The Juris, 2022)
The Criminal Justice System in Indonesia originates from Pancasila, because Pancasila as the source of all laws today has undergone many changes. The components that work in the criminal justice sub-system experience a rapid development which is indirectly influenced by the need for a sense of community justice. Guarantees of legal protection and guarantees of equality before the law, which are constitutional rights for every citizen. The form of the presence of the State is also very necessary, especially the government at the City level, the form of presence in question is to enforce the law in the implementation of Restorative Justice itself. The Samarinda City Government cooperates with the Samrinda City District Attorney to form a Restorative Justice House in the area, this is to provide benefits and justice for the community. Restorative Justice is a law enforcement process by taking into account the principles of fast, simple, and low-cost justice, in order to realize the success of prosecution for justice based on law and conscience, including prosecution using a restorative justice approach which is carried out in accordance with the provisions of the legislation.